Changing trend and influencing factors of nutritional knowledge among Chinese reproductive women - Xiao-li FAN; Gui-ju SUN (Editorial Office of Chinese Journal of Public Health, 2022)
Objective To examine changing trend in nutritional knowledge and its influencing factors among Chinese reproductive women and to provide evidences for the development of targeted nutrition education. MethodsThe data on complete demographic characteristics and dietary knowledge for 13 752 women aged 15 - 49 years were extracted from 5 waves of China Health and Nutrition Survey conducted from 2004 through 2015 in 15 provincial level regions across China. The prevalence of nutritional knowledge in each of the 5 surveys were analyzed and multilevel logistic regression model was applied to investigate influencing factors of nutritional knowledge. ResultsThe number of women surveyed were 2 728，2 597，2 528，3 260, and 2 639 in the year of 2004, 2006, 2009, 2011, and 2015, respectively. In the 5 waves of the survey, the ratio of the participants with nutritional knowledge literacy increased from 0.37% (10/2 728) in 2004 to 48.09% (1 269/2 639) in 2015, with the average growth rates of 963.14% and 2.83% for the periods of 2004 - 2006 and 2006 - 2015. The results of logistic regression analysis on pooled data demonstrated that the women with following characteristics were more likely to have a higher nutritional knowledge: with the education of junior high school (odds radio [OR] = 1.32, 95% confidence interval [95% CI]: 1.12 - 1.56) or senior high school and above (OR = 1.57, 95% CI : 1.32 - 1.86) compared to those with the education of elementary school and below, with higher family annual income per capita (OR= 1.23, 95% CI: 1.10 - 1.38) versus those with the low income, living in central regions (OR = 1.39, 95% CI: 1.18 - 1.63) or eastern regions (OR = 1.90, 95% CI: 1.52 - 2.38) in contrast to those living in western regions, and being aware of food pyramid or dietary guidelines (OR = 1.35, 95% CI: 1.19 - 1.53) in comparison with those without the knowledge. ConclusionAmong Chinese reproductive women, the nutritional knowledge needs to be further improved and the knowledge level is mainly influenced by education, family annual income per capita, living region and the awareness of food pyramid or dietary guidelines.